2013
DOI: 10.1093/ajae/aat040
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Voucher Coupons on the Uptake of Fertilizer and Improved Seeds: Evidence from a Randomized Trial in Mozambique

Abstract: Short-Term Logic and Limitations of Voucher Coupons In the 1970s and early 1980s, a majority of African countries subsidized and sold fertilizer

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 1 publication
0
35
0
Order By: Relevance
“…The input pack was intended for one acre of maize cultivation. Key eligibility criteria for beneficiary farmers included: (i) being unable to afford farm inputs at unsubsidised prices; (ii) 7 To our knowledge, to date the only experimental (randomised-controlled trial, RCT) evaluation of a national or government-piloted ISP in SSA is Carter et al (2013Carter et al ( , 2014. The RCT was conducted in one province in Mozambique.…”
Section: Kenya's National Accelerated Agricultural Inputs Access Progmentioning
confidence: 99%
See 1 more Smart Citation
“…The input pack was intended for one acre of maize cultivation. Key eligibility criteria for beneficiary farmers included: (i) being unable to afford farm inputs at unsubsidised prices; (ii) 7 To our knowledge, to date the only experimental (randomised-controlled trial, RCT) evaluation of a national or government-piloted ISP in SSA is Carter et al (2013Carter et al ( , 2014. The RCT was conducted in one province in Mozambique.…”
Section: Kenya's National Accelerated Agricultural Inputs Access Progmentioning
confidence: 99%
“… To our knowledge, to date the only experimental (randomised‐controlled trial, RCT) evaluation of a national or government‐piloted ISP in SSA is Carter et al . (, ). The RCT was conducted in one province in Mozambique.…”
mentioning
confidence: 99%
“…Finally, drought was also reported to have had a powerful impact on programmes in three cases Mather & Kelly, 2012;Carter et al, 2013). Authors of these studies encourage future input subsidies programmes to include complementary components if farmers are expected to cope with severe-weather-related effects on their crops.…”
Section: Narrative Synthesis Of Implementation and Contextual Factorsmentioning
confidence: 98%
“…Overall, there is a high risk of bias within the sample of included studies (see Figure 3). Only three studies were found to have a low risk of bias (Bardhan & Mookherjee, 2011, Carter et al, 2013, Holden, 2013, with the majority of studies found to have a high risk of bias (n=6). Four studies were rated as having a critical risk of bias due to baseline confounding (Ajayi et al, 2009;Denning, 2009;Kamanga, 2010;Parameswaran, 2012).…”
Section: Risk Of Bias In Included Studiesmentioning
confidence: 99%
“…The experiences of similar types of input subsidy programs in other regions, particularly in sub-Saharan Africa (SSA), have revealed mixed findings. For example, some studies have shown improvements with regards to input use (Carter, Laajaj, & Yang, 2013;Chibwana, Shively, Fisher, Jumbe, & Masters, 2014;Gine, Patel, Cuellar-Martinez, McCoy, & Lauren, 2015), as well as higher yields (Gine, Patel, Cuellar-Martinez, McCoy, & Lauren, 2015). However, the bulk of the evidence from SSA indicates that input subsidy programs are usually Pareto inefficient, that is, the costs generally outweigh the benefits (Jayne and Rashid, 2013).…”
mentioning
confidence: 99%